2006
DOI: 10.1515/jmbm.2006.17.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mechanisms in PMMA/ATH Acrylic Casting Dispersion

Abstract: Acrylic casting dispersion is used to fabricate particulate composites such as poly-methyl methacrylate (PMMA) filled with a fine dispersion alumina trihydrate (ATH). This composite is subjected to severe temperature variations during in-service conditions, giving rise to high thermal stresses which lead to failure by cracking. The influence of the interfacial bond strength between a particle and the matrix on the failure mechanism of acrylic casting dispersion has been investigated using in situ observations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 14 publications
0
3
1
2
Order By: Relevance
“…The results of the tests carried out by the authors showed a significant reduction in the flexural strength of the material under the influence of the raised temperature. The reduction was relatively lower than in the case of tensile strength measured by Nie et al [6], nonetheless it was significant which is of a high practical importance. Another important factor to reduce the bending strength is aging at elevated temperature and humidity, which was described in [4].…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…The results of the tests carried out by the authors showed a significant reduction in the flexural strength of the material under the influence of the raised temperature. The reduction was relatively lower than in the case of tensile strength measured by Nie et al [6], nonetheless it was significant which is of a high practical importance. Another important factor to reduce the bending strength is aging at elevated temperature and humidity, which was described in [4].…”
Section: Resultscontrasting
confidence: 58%
“…Temperature changes have a significant impact on the strength parameters of acrylic-mineral panels. A study of tensile strength of PMMA/ATH panels carried out by Nie et al [6] demonstrated a significant decrease in tensile strength of heated samples of the material. At a temperature of 90 ∘ C, nearly 70% lower tensile strength than at 25 ∘ C was recorded.…”
Section: Results Of Studies Described In Available Literaturementioning
confidence: 99%
“…This is mainly because in particle-filled composites, the toughening effects of the fillers prevent crazing of the polymer matrix (Chee et al 2012). Meanwhile, as shown by Nie et al (2006), the failure of ATH/PMMA composites is initiated by the debonding between filler/matrix and the damage of the PMMA matrix is caused by the growth of the cavity, which happens so fast that crazing cannot be observed. In addition, to simulate the crazing of PMMA, cohesive elements need to be used over the entire RVE (Tijssens et al 2000), which may complicate the model significantly and increase the computational cost.…”
Section: Damage Models and Materials Definitionmentioning
confidence: 99%
“…En la figura se observa que la matriz de PMMA se ha deformado alrededor de las partículas de ATH, con lo cual es posible concluir que no hay una buena adherencia entre las partículas de ATH y la matriz de PMMA. En coherencia con lo señalado por Nie et al [15], la fractura del material habría iniciado con la separación de las partículas de ATH de la matriz de PMMA, lo cual es una señal de una baja fuerza de adhesión entre el refuerzo y la matriz (ausencia de transferencia de carga entre matriz y refuerzo). Puesto que el producto comercial presenta mejores propiedades que los materiales fabricados en este estudio, es probable que para su fabricación se hayan utilizado tratamientos superficiales para mejorar la adhesión interfacial entre el PMMA y ATH, lo cual justificaría razonablemente que presente mejores propiedades mecánicas.…”
Section: Fotografías Sem De La Zona De Fractura De Los Materiales Comunclassified
“…Basaran [14] demuestra que la adhesión entre el refuerzo de ATH y la matriz de PMMA tiene una influencia significativa sobre las propiedades mecánicas. Por su parte, Nie [15] estudió el mecanismo de falla de materiales compuestos de PMMA/MMA en función de la adhesión entre la matriz y el refuerzo. Nie demostró que cuando adhesión entre el PMMA y ATH es alta, la fractura inicia en las aglomeraciones de las partículas de ATH presentes en el material; mientras que cuando la adhesión es baja, la fractura inicia cuando las aglomeraciones de ATH empiezan a separarse de la matriz.…”
Section: Introductionunclassified